Arte como medio cotidiano ante la pandemia 2021 - Granda Carrión, Johanna Del Cisne; Sánchez Mercado, Erick Leonardo (Machala, 2022)
The present research project entitled "Art and Everyday Life", has a very important focus on the realization of a work, with the aim of creating territories in people and artistic references that are available to experience the installation art discipline that involves objects that currently surrounds us. This is how the project aims to create an installation using recycled materials such as cardboard, an element widely used by people for years. The installation and its daily life is a contemporary artistic discipline that emerged in the sixties as an artistic movement, the representation of the work prevails in formal aspects, that is, it presents its experimentation from various materials such as physical, visual or sound. and sometimes the intervention of other artistic disciplines. However, the Spanish Argiles Mónica gives an interpretation that grammatically the term installation comes from the verb to install, a word of daily use that we also use as placing. From this we can deduce that the word installation is nothing more than placing different types of elements or objects in three-dimensional spaces and in coordinated times. The main characteristics that are observed in the artistic work are the play of light through recycled material such as cardboard, making the user able to differentiate the object worked and from what angle the projected figure can be observed, making the mind of our participant play, the content of each chapter will be discussed below: In the first chapter, the conception of the artistic object was discussed, information was sought on how to establish the sculptural installation as a discipline for the realization of the work, therefore, two subtopics were divided, in the first topic, the conceptualization of the object was discussed. artistic, which was integrated to international references that have worked with the installation or recycled materials and in the second chapter we investigate national and local references that have also worked with the same resources with the purpose of obtaining bases for investigative continuity. In the second chapter we will talk about the conception of the artistic work, we will define and conceptualize the work, that is, we will study the materials to work with, their dimensions and the support. As a second point we enter the theoretical foundation, here we collect the fundamental information about the installation. In the third chapter, the process of the work will be observed, starting with pre-production as the main point, the series of sketches and the follow-up of the construction of the final work step by step. In the fourth chapter, the critical approach to the work will be presented, the process developed and the presentation of the work will be discussed through social networks to obtain information and to conclude, the conclusions will be made on how the final and theoretical proposal has been developed.
El presente proyecto investigado titulado “Arte y Cotidianidad”, posee un enfoque muy importante en la realización de una obra, con la finalidad de crear territorios en personas y referentes artísticos que estén dispuestos a experimentar la disciplina artística instalación que involucra objetos que actualmente nos rodea, es así como el proyecto propone como objetivo crear una instalación por medio de materiales reciclados como es el cartón un elemento muy utilizado por las personas desde años atrás. La instalación y su cotidianidad es una disciplina artística contemporánea que surge en la década de los sesenta como un movimiento artístico, la representación de la obra prevalece en aspectos formales es decir, presenta su experimentación a partir de diversos materiales tales como físicos, visuales o sonoros y en ocasiones la intervención de otras disciplinas artísticas. Sin embargo la española Argiles Mónica da una interpretación que gramaticalmente el término instalación proviene del verbo instalar, una palabra de uso cotidiano que también lo empleamos como colocar. A esto podemos se puede deducir que la palabra instalación no es otra cosa que colocar diferentes tipos de elementos u objetos en espacios tridimensionales y en tiempos coordenados. Las características principales que se observara en la obra artística, son el juego de luces a través del material reciclado como el cartón haciendo que el usuario logre diferenciar el objeto trabajado y desde que ángulo que puede observar la figura proyectada haciendo que la mente de nuestro participante juegue, a continuación se hablara del contenido de cada capítulo: En el primer capítulo se trató sobre la concepción del objeto artístico, se buscó información acerca de cómo establecer la instalación escultórica como disciplina para la realización de la obra por ende se dividió dos subtemas, en el primer tema se trato acerca de la conceptualización del objeto artístico, el cual se integró a referentes internacionales que hayan trabajado con la instalación o materiales reciclados y en el segundo capítulo investigamos referentes nacionales y locales que también hayan trabajado con los mismos recursos con el propósito de obtener bases para la continuidad investigativa. En el segundo capítulo platicaremos sobre la concepción de la obra artística, definiremos y conceptualizaremos la obra, es decir estudiaremos los materiales a trabajar, sus dimensiones y el soporte. Como segundo punto entramos a la fundamentación teórica, aquí recopilamos la información fundamental sobre la instalación. En el tercer capítulo se observara el proceso de la obra, iniciando con la preproducción como punto principal, el seriado de bocetos y el seguimiento de la construcción de la obra final paso por paso En el cuarto capítulo se presentara el abordaje crítico de la obra, se hablara del proceso desarrollado y presentación de la obra por medio de redes sociales para obtener información y para culminar se realizara las conclusiones de como se ha venido elaborando la propuesta final y teórico.
Keywords: INSTALACION CONTEMPORANEO; ESCULTURA; ARTE Y COTIDIANIDAD; PROCESO REFLEXIVO; OBJETO